Molecular Identification of Fish Larvae from East Plawangan of Segara Anakan, Cilacap, Central Java, Indonesia - Nuryanto, Agus; Pramono, Hendro; Sastranegara, Moh Husein (Biosaintifika: Journal of Biology & Biology Education, 2017)
Correct identification of fish larvae from East Plawangan is very difficult to be done due to undefined of their morphology, while correct name is an important information for management of that area as spawning and nersery ground. Therefore, so far no scientific report on what species that utilize East Plawangan as their spawning and nursery ground. Cytochrome c oxidase 1 gene provide a precise tool for correct larvae identification. This study aims to test the accuracy of the cytochrome c oxidase 1 gene on fish larvae identification. The COI gene were amplified and sequenced. The homology of sequences were checked using Basic Local Alignment Search Tool (BLAST). Genetic distances were calculated with the help of MEGA 6 software. Taxonomic tree was reconstructed using neighbor-joining and maximum parsimony methods with 1000 bootstraps repeats. A sum of 24 morphotypes were identified, indicating high diversity of fish that utilize East Plawangan as their spawning and nursery ground. BLAST result showed that seven morphotypes were convincingly identified into species level, while three remaining morphotypes could only be identified at generic level. Taxonomic tree shows clear discrimination among morphotypes. This proved that cytochrome c oxidase 1 gene showed high accuracy on larval species discrimination.